Investigation and analysis of the overall rehabilitation nursing needs of hospitalized patients in a certain general hospital (综合医院住院患者整体康复护理需求调查分析) - LIU Xiaoqin (刘晓琴); XU Yulin (徐玉林) (中西医结合护理)
Objective To investigate the overall rehabilitation nursing needs of hospitalized patients in a certain general hospital, and to provide references for establishment of rehabilitation nursing plan. Methods A convenient sampling method was used to investigate hospitalized patients in a certain general hospital in Wuhan by using the self-designed "Resident Care Needs Survey Questionnaire for Inpatients in General Hospitals". Results A total of 280 questionnaires were issued and 264 were returned (response rate of 94. 29%). The overall score was (54.45±14.22) points, indicating a medium level of demand among inpatients. Age, education, and place of residence were influential factors of overall rehabilitation care needs among hospitalized patients(P＜0. 05). Conclusion The results showed a medium level of rehabilitation nursing demand among hospitalized patients. More attentions should be paid to rehabilitation nursing needs of patients with older age, low education level and living in rural areas. (目的 了解综合医院住院患者的整体康复护理需求, 为综合医院制订康复护理计划提供参考和依据。方法 采用方便抽样的方法, 运用自行设计的“综合医院住院患者康复护理需求调查表”对武汉市某三甲综合医院的住院患者进行调查, 并进行统计分析。结果 共发放问卷280份, 有效问卷264(94. 29%)份。综合医院住院患者整体康复护理需求的得分为(54. 45±14. 22)分, 需求程度处于中等水平。年龄、文化程度、居住地是住院患者整体康复护理需求的影响因素(P＜0. 05)。结论 综合医院住院患者整体康复护理需求程度处于中等水平, 应该更加关注高龄、文化程度低和住在偏远地区的住院患者的整体康复护理需求。)